Multifocal subacute osteomyelitis in adjacent bones in the ankle without septic joint - Jeffery D. St. Jeor, BS; Kristen B. Thomas, MD; Paul G. Thacker, MD, MHA.; Nathan C. Hull, MD (Radiology Case Reports, 2020)
Osteomyelitis is an inflammation involving bone and/or bone marrow most often the result of bacterial infection of the bone. In children, osteomyelitis most often has an acute presentation and is caused by hematogenous spread. When osteomyelitis is seen in the extremities, conventional radiography is the first-line imaging modality preformed for diagnosis with magnetic resonance imaging employed for further delineation or as a problem-solving tool. A healthy 6-year-old female presented with a history of nonspecific left leg pain for 3-5 weeks which gradually progressed to focal left ankle pain and swelling. Further workup revealed multifocal subacute osteomyelitis with Brodie's abscesses seen on imaging in the absence of a septic joint. This was an uncommon presentation for the following reasons: Patients with multifocal osteomyelitis usually present in the acute setting, as opposed to the subacute setting. When osteomyelitis is multifocal or Brodie's abscesses are present adjacent to the joint capsule, concomitant septic joint is commonly seen.